Bank regulation and supervision a decade after the global financial crisis. (Global financial development report ;, 2020)
Over a decade has passed since the collapse of the U.S. investment bank, Lehman Brothers, marked the onset of the largest global economic crisis since the Great Depression. The crisis revealed major shortcomings in market discipline, regulation and supervision, and reopened important policy debates on financial regulation. Since the onset of the crisis, emphasis has been placed on better regulation of banking systems and on enhancing the tools available to supervisory agencies to oversee banks and intervene speedily in case of distress. Drawing on ten years of data and analysis, Global Financial Development Report 2019/2020 provides evidence on the regulatory remedies adopted to prevent future financial troubles, and sheds light on important policy concerns. To what extent are regulatory reforms designed with high-income countries in mind appropriate for developing countries? What has been the impact of reforms on market discipline and bank capital? How should countries balance the political and social demands for a safety net for users of the financial system with potentially severe moral hazard consequences? Are higher capital requirements damaging to the flow of credit? How should capital regulation be designed to improve stability and access? The report provides a synthesis of what we know, as well as areas where more evidence is still needed.